GAMMA RADIATION TRANSPORT IN THE PRESENCE OF NUCLEAR RESONANT SCATTERING GAMMA IN UNIFORM MEDIA - Bravo Cabrejos, Jorge A. (2000)
The energy dependent transport equation for X- and gamma radiation in a uniform medium is formulated. This medium contains trace amounts of an isotopic species capable of absorbing and emitting gamma radiation resonantly thanks to the Mössbauer effect. This equation is solved exactly for the case of an infinite medium and approximately for the case of a flat foil. These results are applied to the case of a radiactive Co-57 Mössbauer source in a metallic matrix to determine the spectral characteristics of self-absorption in the source matrix.